1996
DOI: 10.1113/jphysiol.1996.sp021781
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of vagal mucosal afferents to cholecystokinin and its role in afferent signal transduction in the rat.

Abstract: 1. Extracellular recordings from rat mesenteric paravascular nerve bundles were made in order to characterize the responses of different populations of afferents supplying the small intestine to intravenous cholecystokinin (CCK; in the form of sulphated CCK8). 2. Approximately 70% of mesenteric nerve bundles contained CCK‐sensitive afferent fibres. Responsive afferents had low spontaneous discharge (1.6 +/‐ 0.3 impulses s‐1) and showed a 14‐fold increase in firing at the peak of the response to 50 pmol CCK wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
55
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 23 publications
(22 reference statements)
8
55
0
1
Order By: Relevance
“…Blackshaw & Grundy (1990) concluded their study by suggesting that although activation of mucosal fibres from the gut by luminal stimuli has weak effects on vagal efferent fibre discharge, the reflexogenic potency may be enhanced if a large number of mucosal afferents would be stimulated simultaneously. Richards et al (1996) provided further evidence in anaesthetised rats by showing that mesenteric nerve bundles contained one to two afferent fibres responding to CCK8 in a dose-related manner (threshold dose , 5 pmol), and that the administration of CCK 1 -receptor antagonist (devazepide) abolished an enhanced discharge in vagal afferent fibres induced by CCK8 application. The CCK-sensitive subpopulations of mesenteric afferent nerves slowly adapted to luminal hydrochloric acid and were not sensitive to intestinal distension.…”
Section: Global Effects Of Gastrin and Cholecystokinin In The Gutmentioning
confidence: 98%
“…Blackshaw & Grundy (1990) concluded their study by suggesting that although activation of mucosal fibres from the gut by luminal stimuli has weak effects on vagal efferent fibre discharge, the reflexogenic potency may be enhanced if a large number of mucosal afferents would be stimulated simultaneously. Richards et al (1996) provided further evidence in anaesthetised rats by showing that mesenteric nerve bundles contained one to two afferent fibres responding to CCK8 in a dose-related manner (threshold dose , 5 pmol), and that the administration of CCK 1 -receptor antagonist (devazepide) abolished an enhanced discharge in vagal afferent fibres induced by CCK8 application. The CCK-sensitive subpopulations of mesenteric afferent nerves slowly adapted to luminal hydrochloric acid and were not sensitive to intestinal distension.…”
Section: Global Effects Of Gastrin and Cholecystokinin In The Gutmentioning
confidence: 98%
“…The strongest indirect evidence comes from the generally accepted view that CCK's effect on vagal afferents is paracrine rather than endocrine. This view is mainly based on the observations that 1) vagal mucosal afferents show an extraordinary sensitivity to CCK that is not mediated by smooth-muscle motor effects (Richards et al, 1996); 2) food intake suppression induced by intraduodenal infusion of various nutrients is not correlated with the obtained plasma CCK increases (Brenner et al, 1993); and 3) vagal afferent terminals are in close proximity to the site of CCK release from enteroendocrine cells (Berthoud and Patterson, 1996). This paracrine hypothesis assumes that CCKA receptors are located on mucosal terminals of primary vagal afferents.…”
Section: Cckar-immunoreactivity In the Duodenummentioning
confidence: 99%
“…Richards et al (27) found that administration of the CCK-A receptor antagonist MK-329 blocked excitation of vagal afferents by CCK. However, this population of afferents was not excited by distension of the intestine.…”
mentioning
confidence: 99%